2019
DOI: 10.1021/acschembio.9b00481
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Targeting TDP-43’s RNA Recognition Motifs Reduces Locomotor Defects in a Drosophila Model of Amyotrophic Lateral Sclerosis (ALS)

Abstract: RNA dysregulation likely contributes to disease pathogenesis of amyotrophic lateral sclerosis (ALS) and other neurodegenerative diseases. A pathological form of the transactive response (TAR) DNA binding protein (TDP-43) binds to RNA in stress granules and forms membraneless, amyloid-like TDP-43 aggregates in the cytoplasm of ALS motor neurons. In this study, we hypothesized that by targeting the RNA recognition motif (RRM) domains of TDP-43 that confer a pathogenic interaction between TDP-43 and RNA, motor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…Supporting a role for RNA as a factor inducing toxicity is the recent identification of small molecules that can bind TDP-43 and displace G quadruplex like structures but not canonical UG repeats. Notably, one of these structures identified using in silico design also mitigates TDP-43 dependent toxicity in vivo, in a Drosophila model of ALS (Francois-Moutal et al, 2019). Although it remains to be determined whether this small molecule works in vivo by actually binding TDP-43 and displacing mRNA targets, the findings provide proof of principle that targeting the RRM domain of TDP-43 may provide strategies for mitigating toxicity at least in the context of TDP-43 overexpression.…”
Section: Rna As a Toxic Factormentioning
confidence: 89%
“…Supporting a role for RNA as a factor inducing toxicity is the recent identification of small molecules that can bind TDP-43 and displace G quadruplex like structures but not canonical UG repeats. Notably, one of these structures identified using in silico design also mitigates TDP-43 dependent toxicity in vivo, in a Drosophila model of ALS (Francois-Moutal et al, 2019). Although it remains to be determined whether this small molecule works in vivo by actually binding TDP-43 and displacing mRNA targets, the findings provide proof of principle that targeting the RRM domain of TDP-43 may provide strategies for mitigating toxicity at least in the context of TDP-43 overexpression.…”
Section: Rna As a Toxic Factormentioning
confidence: 89%
“…414-Residue TDP-43 contains two folded RRM domains (Fig. 1 A), which are not only essential for recognizing UG-rich sequences near RNA splice sites 11 , but also extensively demonstrated to participate in disease-causing aggregation/fibrillation in additional to its C-terminal prion-like domain 11 19 . Remarkably, small molecules targeting the RRM domains of TDP-43 have been recently identified to reduce locomotor defects in drosophila model of ALS 19 .…”
Section: Introductionmentioning
confidence: 99%
“…1 A), which are not only essential for recognizing UG-rich sequences near RNA splice sites 11 , but also extensively demonstrated to participate in disease-causing aggregation/fibrillation in additional to its C-terminal prion-like domain 11 19 . Remarkably, small molecules targeting the RRM domains of TDP-43 have been recently identified to reduce locomotor defects in drosophila model of ALS 19 . We also found that ATP, the universal energy currency, specifically binds the RRM domains of FUS and TDP-43 to inhibit their amyloid fibrillation 20 22 .…”
Section: Introductionmentioning
confidence: 99%
“…1A), which are not only essential for recognizing UG-rich sequences near RNA splice sites (11), but also extensively demonstrated to participate in disease-causing aggregation/fibrillation in additional to its Cterminal prion-like domain (11)(12)(13)(14)(15)(16)(17)(18)(19). Remarkably, small molecules targeting the RRM domains of TDP-43 have been recently identified to reduce locomotor defects in drosophila model of ALS (19). We also found that ATP, the universal energy currency, specifically binds the RRM domains of FUS and TDP-43 to inhibit their amyloid fibrillation (20)(21)(22).…”
mentioning
confidence: 99%
“…Briefly, the FUS RRM domain undergoes fibrillation not only due to its relatively low stability with melting temperature (Tm) of 55 ºC, lower than that of the human gS-crystallin with Tm of 71 ºC (24), but also resulting from its high conformational dynamics, that allow the dynamic opening of the structure to expose its central hydrophobic regions for aggregation/fibrillation (23). Consequently, although ATP induces no enhancement of the thermal stability of the FUS RRM domain, it is sufficient to kinetically inhibit the amyloid fibrillation through weak but specific binding with a Kd of 3.77 mM to a pocket within the conserved nucleic-acid-binding surfaces, which thus leads to blocking the dynamic opening of the structure (19).…”
mentioning
confidence: 99%